SURAT SEBAGAI MEDIA DAKWAH: Studi Atas Praktek Dakwah Rasulullah saw terhadap Raja Heraclius, Kisra Abrawaiz, Muqouqis, dan Najasyi - Bobby Rachman Santoso; Umul Baroroh; Asep Dadang Abdullah (Jurnal Ilmu Dakwah, 2015)
It was proven that the letter format of the Prophet delivered to the kings during his da’wah was astounding. His letters being written by Zaid bin Thabit were always preceded by Basmalah word, whereas the letters were sent to unbelievers. This study is a kind of descriptive qualitative research that used a historical approach. The result shows that there were some reasons behind the Prophet messages as a medium of da’wah to the kings: a) it was a result of the Hudaybiya Peace Treaty and the success of the Prophet on establishing Muslims force in Medina. It was influenced by the conflict between King Heraclius and King Kisra Abrawaiz. b) the Prophet’s letters were likely to show that the Prophet Muhammad was the Medina leader. c) it was triggered by the universality of Muhammad prophet-hood as a leader of mankind, as well as the crisis of confidence experienced by Najasyi and Muqouqis.***Format surat dakwah Rasulullah saw yang dikirimkan kepada para raja sangatlah menkajubkan. Surat-surat Rasulullah saw yang ditulis oleh sekretarisnya yakni Zaid bin Tsabit selalu didahului kalimat Basmalah, padahal surat-surat itu akan dikirimkan kepada orang-orang kafir. Jenis penelitian ini kualitatif dengan menggunakan pendekatan historis, sedangkan spesifikasi penelitian yang digunakan adalah deskriptif. Hasil penelitian ini yaitu ada beberapa latar belakang pengiriman surat sebagai media dakwah:  a) akibat Perjanjian Perdamaian Hudaibiyah, keberhasilan Rasulullah saw membentuk kekuatan umat muslim di Madinah,  dan konflik yang terjadi antara Raja Heraclius dan Kisra Abrawaiz. b) surat Rasulullah saw. yang bernuansa politik ingin menunjukkan bahwa beliau adalah pemimpin Madinah. c) universalitas kenabian Muhammad saw sebagai pemimpin umat manusia, serta krisis kepercayaan yang dialami Najasyi dan Muqouqis